2020
DOI: 10.1126/scitranslmed.aba8014
|View full text |Cite
|
Sign up to set email alerts
|

Bioadhesive hydrogels demonstrating pH-independent and ultrafast gelation promote gastric ulcer healing in pigs

Abstract: Hydrogels are soft materials used in an array of biomedical applications. However, the in situ formation of hydrogels at target sites, particularly in dynamic in vivo environments, usually requires a prolonged gelation time and results in poor adhesion. These limitations cause considerable loss of both hydrogel mass and encapsulated therapeutic cargoes, thereby compromising treatment outcomes. Here, we report the development of a hydrogel based on thiourea-catechol reaction to enhance the bioadhesion. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(151 citation statements)
references
References 57 publications
(73 reference statements)
2
137
0
1
Order By: Relevance
“…We further compared the underwater adhesiveness of Gel–GS by using lap‐shear adhesion test. [ 30 ] The results showed that the adhesive strength of the hydrogel decreases after being immersed in phosphate‐buffered saline (PBS), which may be due to weakening of the hydrogen bonding interactions between the hydrogel and tissue (Figure S10, Supporting Information). However, the underwater adhesive strength does not change significantly over time (from 1 to 12 h), which indicated the Gel–CS hydrogel remains adhered to the tissue even underwater.…”
Section: Resultsmentioning
confidence: 99%
“…We further compared the underwater adhesiveness of Gel–GS by using lap‐shear adhesion test. [ 30 ] The results showed that the adhesive strength of the hydrogel decreases after being immersed in phosphate‐buffered saline (PBS), which may be due to weakening of the hydrogen bonding interactions between the hydrogel and tissue (Figure S10, Supporting Information). However, the underwater adhesive strength does not change significantly over time (from 1 to 12 h), which indicated the Gel–CS hydrogel remains adhered to the tissue even underwater.…”
Section: Resultsmentioning
confidence: 99%
“…The catechol groups in pH 2 buffers were less oxidized than the catechol groups in pH 7.4 buffer as evidenced by the less pronounced quinone peak (around 400 nm) in UV–vis absorption spectra (Figure S9, Supporting Information). [ 16 ] Therefore, the striking contrast between the vacuole stability at pH 2 and pH 7.4 indicates that the fusion‐resistant stability of the vacuoles is due to the consumption of catechol by oxidation at pH 7.4 and the associated increase in cross‐linking density. The significantly increased diameter of vacuoles within N 2 ‐protected NPA (H 1 ) coacervate under a physiological environment (pH 7.4, 37 °C) further revealed the role of catechol–quinone oxidation in stabilizing the vacuoles over time (Figure S10, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…Meanwhile, in recent years, plenty of experimental hemostatic materials have been developed and used for rapid wound sealing and bleeding control, including sponges or foams, microspheres or beads, gauzes or zeolites, and functional hydrogels [ 49 , 50 ]. Previous studies have proven that some of these materials show the ability to control mild bleeding of artery or heart and promote wound healing [ 34 , 51 ]. However, because of slow hemostatic performance, low hemostatic efficacy, poor mechanical strength and flexibility, these hemostats are ineffective or unsuitable for treating aortic trauma or large/irregular wounds.…”
Section: Resultsmentioning
confidence: 99%